A Multicenter, Randomized, Controlled Trial of Rebamipide Plus Lansoprazole for the Treatment of Postendoscopic Submucosal Dissection Ulcers. Issue 1 (January 2019) - Yan, Bin; Lu, Zhongsheng; Ge, Zhizheng; Liu, Side; Guo, Xuegang; Tian, Dean; Yang, Yuxiu; Li, Xiaobo; Gong, Wei; Liu, Zhiguo; Liu, Mei; Zhou, Bingxi; et al.
Abstract : OBJECTIVES: To evaluate the healing efficacy of rebamipide and lansoprazole combination therapy with lansoprazole alone for endoscopic submucosal dissection (ESD)–induced ulcers and clarify the ulcer healing-associated factors. METHODS: Three hundred patients were randomized into control and experimental groups after they underwent ESD. The patients received intravenous pantoprazole (30 mg) every 12 hours and oral rebamipide (100 mg, experimental group) or placebo (control group) 3 times daily on days 1–3. On days 4–56, patients received oral lansoprazole (30 mg daily) and rebamipide (100 mg) or placebo 3 times daily. Endoscopic evaluations were performed at postoperative weeks 4 and 8. RESULTS: At week 4, the ulcer reduction rate was significantly higher in the experimental than in the control group (0.97 ± 0.034 vs. 0.94 ± 0.078; P < 0.001). The ulcer healing (18.2% vs 20.3%; P = 0.669) and ulcer improvement rates (94.2% vs 88.7%; P = 0.109) in the 2 groups were not significantly different. At week 8, the ulcer healing and ulcer improvement rates were 90.6% and 100%, respectively, in both groups. Multivariate analysis showed that the combination treatment was an independent factor associated with ulcer area reduction after ESD. The maximum diameter of the initial ulcer (≥35.5 mm vs <35.5 mm) was an independent factor associated with the ulcer improvement rate after ESD. CONCLUSIONS: The rebamipide and lansoprazole combination therapy can help accelerate the reduction rate of post-ESD ulcer compared with the lansoprazole monotherapy at 4 weeks of therapy.